Narrative architecture reframing community perceptions of industrial waste management facilities - Gayatin, Denise Angelica L.; Joson, Gerard Thomas F. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Each year the Philippines grows more and more populated. By 2050, it is predicted that sixty-five percent of the total population will live in cities. Therefore, in order to offer a more holistic approach to the issues of rapid urbanization, there must be greater investment in outlying urban areas in order to increase productivity and create jobs outside of the National Capital Region. With the help of mass transportation to bridge NCR to these areas, proper infrastructure must also be built to preparer for the influx in economic development. Being a peri-urbanized area of Bulacan, Mecauayan has several industrial parks which pose both opportunities and problems to the community. The life cycle of the waste from these industries can be reinvented. Through modern interventions, there is a strong potential to turn the ills of industrialization into an economically beneficial and sustainable endeavor. Materials recovered from the waste stream must be redirected to facilities which can transform them through chemical recycling. This provides opportunity for a more circular economy and sustainable practices of industrial areas. This study aims to create the design of a metal recovery and recycling facility that transforms scrap metals and unusable precious metals so that they can be given new life, facilitates research and development in the field of materials recycling process, encourages community awareness and involvement in waste management, and promotes Meycauayan as a leader in metals recovery and sustainable industry practices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Industrial facilities -- Mecauayan, Bulacan; Refuse and refuse disposal; Solid waste management complex -- Mecauayan, Bulacan